2010
DOI: 10.1080/14786410903246868
|View full text |Cite
|
Sign up to set email alerts
|

Determination of then-alkane profile of epicuticular wax extracted from mature leaves ofCestrum nocturnum(Solanaceae: Solanales)

Abstract: An n-hexane extract of fresh, mature leaves of Cestrum nocturnum (Solanales: Solanaceae) containing thin layer epicuticular waxes was analysed by thin-layer chromatography, infrared and gas liquid chromatography using standard hydrocarbons. Seventeen long chain alkanes (n-C(18) to n-C(34)) were identified and quantified. Hentriacontane (n-C(31)) was established as the major n-alkane, while nonadecane (n-C(19)) was the least abundant component of the extracted wax fraction. The carbon preference index calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The variations in n-alkane content and levels throughout the developmental stages of leaves occur due to change in the rate of wax production after leaf emergence (Piasentier et al, 2000), and the results of the present study are consistent with the hypothesis that the amount and composition of nalkanes in the leaves change depending on the developmental age of leaves (Hellmann andStoesser, 1992, Dutton et al, 2000;Jetter and Schaffer, 2001). Further, Piasentier et al (2000), Barik et al (2004), Chowdhury et al (2010) demonstrated that n-C27, n-C25, and n-C31 were the predominant n-alkanes in the epicuticular wax of leaves of beech, Ludwigia adscendens, and Cestrum nocturnum, respectively; but in the present study, n-C29 was the predominant n-alkane in young and mature sunflower leaves and n-C23 was the most abundant alkane in senescent leaves. The odd number n-alkanes were clearly predominant throughout the developmental state of sunflower leaves, which is in good agreement with the findings of previous observation carried out on six browsed broad leaf trees (Piasentier et al, 2000).…”
Section: Resultscontrasting
confidence: 57%
“…The variations in n-alkane content and levels throughout the developmental stages of leaves occur due to change in the rate of wax production after leaf emergence (Piasentier et al, 2000), and the results of the present study are consistent with the hypothesis that the amount and composition of nalkanes in the leaves change depending on the developmental age of leaves (Hellmann andStoesser, 1992, Dutton et al, 2000;Jetter and Schaffer, 2001). Further, Piasentier et al (2000), Barik et al (2004), Chowdhury et al (2010) demonstrated that n-C27, n-C25, and n-C31 were the predominant n-alkanes in the epicuticular wax of leaves of beech, Ludwigia adscendens, and Cestrum nocturnum, respectively; but in the present study, n-C29 was the predominant n-alkane in young and mature sunflower leaves and n-C23 was the most abundant alkane in senescent leaves. The odd number n-alkanes were clearly predominant throughout the developmental state of sunflower leaves, which is in good agreement with the findings of previous observation carried out on six browsed broad leaf trees (Piasentier et al, 2000).…”
Section: Resultscontrasting
confidence: 57%
“…Significant differences of individual and total n-alkane concentration in plant leaves have been reported (Barik, Bhattacharya, Laskar and Banerjee, 2004). Further, Dutton, Mattiacci and Dorn (2000), Hellman and Stoesser (1992), Piasentier et al (2000) and Chowdhury et al (2010) reported that n-C 27 (heptacosane), n-C 31 (hentriacontane) and n-C 33 (tritriacontane) were the most prominent alkanes present in epicuticular waxes. The present study shows similar results with variation of n-alkanes all through the year.…”
Section: Results and Disscussionmentioning
confidence: 96%
“…The balance was made up of an unknown number of unidentified branched chain alkanes (31.18%). Hexadecane (5.92%), heptadecane (6.18%) hentriacontane (5.47%), nonacosane (5.29%) and heptacosane (5.11%) were the more abundant n-alkanes, whilst docosane was the least abundant (2.16%).The main component of epicuticular waxes of plant leaves were higher alkanes where the alkanes having odd number of carbons predominate (Saber et al, 2010;Chowdhury et al, 2010). There was a significant difference in the individual and total n-alkane concentrations in tree leaves (Piasentier et al, 2000;Jetter and Schaffer, 2001).…”
Section: Resultsmentioning
confidence: 99%